From lean to reconfigurability: systematic review of high performance manufacturing - César H. Ortega Jiménez; José A. Domínguez Machuca; Pedro Garrido Vega (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
Both the implementation of reconfigurable manufacturing systems (RMS) and its integration to current practices (e.g. human resources, information technology, etc.) being used within manufacturing plants are of fundamental concern to fields associated with business administration and management Hence, since specialized literature states RMS's effective operation will encircle lean manufacturing, this paper uses it as a foundation. While there has been significant study of lean operations, it is often piece-meal as diverse models are hypothesized and empirically tested. This paper attempts to examine the models purporting to study the fundamental question of the use of lean within a high performance manufacturing (HPM) framework. Models examining lean-HPM programs-performance relationship are summarized and reviewed systematically in an attempt to provide a more integrated perspective of lean and the factors that interact with it to enhance manufacturing performance to have a general representation of the HPM stage for RMS deployment. The models are evaluated on their common dimensions, and insights for further research are identified. A research plan, along with a research model, is proposed with the hope of facilitating future work in the implementation and operations of RMS, as an area of imminent and growing importance of having high responsiveness in ever changing markets.
Keywords: 650; Lean; High performance manufacturing (HPM); Just in time (JIT); Reconfigurable manufacturing system (RMS); Responsiveness